Ureteroscope-aided Reinsertion of Dislodged Pigtail Nephrostomy Tube Through Collapsed Tract - Chang, Shun-Kai; Chen, Bo-Jung; Jou, Yeong-Chin; Li, Min-Chun; Chen, Pei-Yi (Urology Journal, 2019)
Purpose: To introduce an alternative method for the reinsertion of pigtail catheter for collapsed nephrostomy tract. Materials and Methods: Between January 2013 and October 2016, a total of ten patients with collapsed nephrostomy tract underwent ureteroscope-aided reinsertion of the pigtail catheter after the failure of manual reinsertion by guidewire. Under local anesthesia, the ureteroscope was inserted through a percutaneous nephrostomy (PCN) opening. The access path was obtained by careful tracing for prior placement of pigtail catheter. The clinical features of these ten patients, including operation time, success rate and complications, were evaluated by retrospective chart review. The Clavien classification was applied to define the grade of complications after one-month follow-up. Results: Among the ten cases of difficult PCN revision, eight underwent the procedure within 24 hours of the dislodgement. The remaining two patients underwent the procedure within 2 days and 8 days. The period of pigtail tube dwelling ranged from 2 weeks to 10.5 months. The procedure was successful in nine cases and the operation time ranged from 10 to 30 minutes. No fluoroscope was used in any patient. All of the nine patients had a good drainage function after tube reinsertion. Complications occurred only in one patient who had postoperative fever classified as Clavien grade 2. Conclusion: Reinserting the dislodged pigtail nephrostomy tube with the aid of an ureteroscope is an alternative method that may decrease the necessity of new tract creation.